Acibenzolar‐S‐methyl may prevent vector‐mediated flavescence dorée phytoplasma transmission, but is ineffective in inducing recovery of infected grapevines. Issue 3 (26th May 2016) - Miliordos, Dimitrios E; Galetto, Luciana; Ferrari, Ester; Pegoraro, Mattia; Marzachì, Cristina; Bosco, Domenico
Abstract: BACKGROUND: Acibenzolar‐ S ‐methyl (BTH), a functional analogue of salicylic acid (SA), is known to elicit a systemic resistance across a broad range of plant–pathogen interactions, but so far it has not been tested against flavescence dorée (FDP), one of the most devastating grapevine diseases. The aim of this work was to evaluate the activity of BTH in preventing FDP transmission by the insect vector and in inducing recovery of infected grapevines. RESULTS: Repeated 2 mM applications of BTH to test grapevine cuttings (cv. Barbera) exposed to adults of the infectious vector Scaphoideus titanus Ball reduced the rate of infected plants. The effect was not recorded following similar BTH applications to highly susceptible young in vitro propagated vines. A high natural recovery rate (more than 70%) was observed over a 3 year period in field‐infected grapevines of the same cultivar. Under these conditions, BTH repeated applications over the whole period clearly failed to increase recovery of field‐infected grapevines. CONCLUSION: Following a 3 year experiment, it can be concluded that, although high doses and repeated applications of BTH reduced vector transmission of FDP, BTH was ineffective in inducing recovery of FDP‐infected grapevines cv. Barbera under field conditions. © 2016 Society of Chemical Industry